Functional coefficient panel modeling with communal smoothing covariates - PHILLIPS, Peter C. B. (Institutional Knowledge at Singapore Management University, 2022)
Behavior at the individual level in panels is often influenced by aspects of the system in aggregate. In particular, the interaction between individual-specific explanatory variables and an individual dependent variable may be affected by 'global' variables that are relevant in decision making and shared communally by all individuals in the sample. To capture such behavioral features, we employ a functional coefficient panel model in which certain communal covariates may jointly influence panel interactions by means of their impact on the model coefficients. Two classes of estimation procedures are proposed, one based on cross-section averaged data, the other on the full panel. The asymptotic properties of these methods are obtained and compared, allowing for sequential and joint expansion of the cross-section and time series sample sizes. Limit theory for the associated fixed effects estimators is derived and inferential procedures are developed to test hypotheses concerning the functional coefficients. The finite sample performance of the proposed estimators and tests are examined by simulation. An empirical illustration is provided in which the regional sensitivity of housing rental prices to available job numbers is studied with national labor force participation rate as the communal smoothing covariate. Strong evidence is found supporting the functional coefficient specification with this country-wide smoothing variable. (C) 2021 Elsevier B.V. All rights reserved.